Racism : a very short introduction - Rattansi, Ali (Very short introductions ;, 2007)
Racism exists in many different forms, in almost every facet of society. This Very Short Introduction demystifies the subject and explores its history, science, and culture. Shedding light on how racism has evolved since its earliest beginnings, and examining the notion of race from a modern genetic viewpoint, Ali Rattansi considers the numerous embodiments of racism - from ethnic cleansing and cultural imperialism to discrimination in politics and everyday life. - ;From subtle discrimination in everyday life and scandals in politics, to incidents like lynchings in the American South, cultural.